2006
DOI: 10.1088/0953-8984/18/47/004
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial ordering of nitrogen and carbon in laser nitrided and laser carburized austenitic stainless steel

Abstract: The distribution of carbon and nitrogen atoms on the octahedral interstitial sites of the face-centred-cubic austenite phase in Fe–C and Fe–N alloys, especially in austenitic stainless steel, is still causing controversy. In this work, results of Mössbauer experiments are presented in order to advance the understanding of this interstitial occupation. Therefore, laser carburized and laser nitrided austenitic stainless steel was investigated by means of x-ray diffraction and Mössbauer spectroscopy. Three subspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…Similarly for published results on the crystal structure, available literature on Mössbauer studies and magnetic properties of expanded austenite is focused on specimens with gradients in composition and residual stresses [7,20,21,[24][25][26][27], which is likely to influence the obtained results. In the current investigation the relation between interstitial content and magnetic properties is, for the first time, explored for homogeneous samples of nitrogen expanded austenite.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly for published results on the crystal structure, available literature on Mössbauer studies and magnetic properties of expanded austenite is focused on specimens with gradients in composition and residual stresses [7,20,21,[24][25][26][27], which is likely to influence the obtained results. In the current investigation the relation between interstitial content and magnetic properties is, for the first time, explored for homogeneous samples of nitrogen expanded austenite.…”
Section: Introductionmentioning
confidence: 99%
“…Mossbauer spectroscopy is a powerful tool in probing the variation in the local environment of iron atoms in ferrous alloys [84][85][86][87][88] Lei and Zhu [90] applied AES and XPS to study the expanded austenite phase formed on plasma nitride 18-8 austenitic stainless steel and found that, all the chromium and part of the iron were in the nitride state and all the nickel was in metallic state. As compared to stoichiometric nitrides, the nitrided phase contains weaker Cr-N ionic-type bonds and stronger Fe-N ionic-type bonds.…”
Section: Structural-chemical Characterization By Mossbauer Spectroscopymentioning
confidence: 99%
“…Nitrogen is known to occupy interstitial sites in AISI 316 which results in hardening. [42] Additional strengthening mechanisms are associated with the formation of nitrides. With involvement of the alloying elements in AISI 316, the reported values can be explained by CrN/Cr 2 N nitrides (which are difficult to identify in XRD) accompanied with the formation of e-Fe 2 N-Fe 3 N nitrides.…”
Section: Microhardness Of Nitrided Stainless Steel Filmsmentioning
confidence: 99%